Impact of Executive Remuneration and Firm Leverage on Firm Stability: Lessons from European Firms - Nasrin, Farjana (Journal of Asian Business Strategy, 2022)
The aim of this study is to examine the impact of executive remuneration and firms’ leverage on firms’ stability as measured by winsorized Zscore (wZscore). The wZscore measure corresponds to the Altman Zscore, which increases as default risk decreases. To test the study’s hypotheses, a linear regression model is applied to a 6-year panel dataset of 180 listed firms categorized in 10 economic sectors operating in 22 countries from the years 2013 to 2018. The results show that executive remuneration has a significant negative impact on firm stability as measured by wZscore. Additionally, firm leverage has a significant positive impact on firm stability. Beyond the theoretical implications, the findings of this study have some practical implications that are particularly relevant to boards of directors, shareholders, managers, and policymakers. The findings suggest that executives should be offered a proper remuneration package to maintain their firms’ stability along with the capacity of firms’ equity and assets to cope up with unprecedented circumstances and the firms’ long-term debts. Finally, this study offers specific recommendations for how firms can balance their pay and performance in terms of executive remuneration and ensure better leverage to optimize their own and society’s sustainable development.